Analisis Yuridis Perjanjian Sewa Menyewa Peralatan Pernikahan Antara Wedding Organizer Dengan Konsumen: (Studi Kasus Di Wedding Organizer Shinta Boyolali) - Humam Rafii, Tegar; Jaya Subadi, Eka (Faculty of Law, University of Mataram, 2024)
Purposes of this study are to know and to explain agreement forms in Shinta Wedding Organizer and forms of dispute settlement in rent agreement between wedding organizer and consumer. Type of this study was empirical legal research which applied statute, conceptual, and sociological approach. Based on the obtained research’s result, it can be stated that the contracts are conducted in two ways, are verbally based on mutual trust principle and written in the form of unregistered contract with specific duty stamp. However, forms of dispute settlement of wedding equipment rent agreement will be initially through non-litigation, but this process is not final, since the court proceedings is the last and final procedure.